Absence of Glutathione S-Transferase Theta 1 Gene Is Significantly Associated With Breast Cancer Susceptibility in Pakistani Population and Poor Overall Survival in Breast Cancer Patients: A Case-Control and Case Series Analysis - Ajaz, Sadia; Zaidi, Sani-e-Zehra; Ali, Saleema Mehboob; Siddiqa, Aisha; Memon, Muhammad Ali; Firasat, Sadaf; Abid, Aiysha; Khaliq, Shagufta (Frontiers in Oncology, 2021)
Deletion of Glutathione S-Transferase Theta 1 (GSTT1) encoding gene is implicated in breast cancer susceptibility, clinical outcomes, and survival. Contradictory results have been Zeported in different studies. The present investigation evaluated GSTT1-absent genotype for its contribution to breast cancer risk in Pakistani population and specific clinical outcomes in breast tumours. A prospective study comprising case-control analysis and case series analysis components was designed. Peripheral blood samples were collected from enrolled participants. After DNA extraction, GSTT1 genotyping was carried out by a multiplex PCR with β-globin as an amplification control. Association evaluation of GSTT1 genotypes with breast cancer risk, specific tumour characteristics, and survival was the primary endpoint. A total of 264 participants were enrolled in the molecular investigation (3 institutions). The study included 121 primary breast cancer patients as cases and 143 age- matched female subject, with no history of any cancer, as controls. A significant genetic association between GSTT1-absent genotype and breast cancer susceptibility (p-value: 0.003; OR: 2.13; 95% CI: 1.08-4.29) is reported. The case-series analysis showed lack of association of GSTT1 genotypes with tumour stage (p-value: 0.12), grade (p-value: 0.32), and size (p-value: 0.07). The survival analysis revealed that GSTT1-absent genotype cases had a statistically significant shorter overall survival (OS) than those with GSTT1-present genotype cases (mean OS: 23 months vs 33 months). The HR (95% CI) for OS in patients carrying GSTT1-absent genotype was 8.13 (2.91-22.96) when compared with GSTT1-present genotype. The present study is the first report of an independent, population-oriented significant genetic association between GSTT1-absent genotype and breast cancer susceptibility as well as OS in breast cancer cases. Upon further validation, GSTT1 variation may serve as a marker for devising better and population-specific strategies for screening and treatment in breast cancer management.